CD8+ T cells contribute to the development of transplant arteriosclerosis despite CD154 blockade. - Ensminger, S; Witzke, O; Spriewald, B; Morrison, K; Morris, P; Rose, M; Wood, K (2000)
BACKGROUND: The CD40-CD154 receptor-ligand pair plays a critical role in allograft rejection by mediating the activation of endothelial cells, antigen-presenting cells, and T cells. Blockade of this interaction prevents acute allograft rejection and leads to prolonged allograft survival in numerous experimental models, but in most cases indefinite graft survival is not achieved due to evolving transplant arteriosclerosis. In this study, we have used a model of transplant arteriosclerosis to investigate whether CD4+ and CD8+ T cells are differentially affected by CD154 blockade. METHODS: BALB/c (H2d) aortic grafts were transplanted into C57BL/6 (H2b) recipients treated with anti-CD154 monoclonal antibody in the presence or absence of CD8+ T-cell depletion. Histology and morphometric measurements were performed on day 30 after transplantation. RESULTS: Only combined treatment with anti-CD154 and anti-CD8 monoclonal antibodies resulted in a significant reduction of intimal proliferation (33 +/-10% vs. 67+/-14%; untreated control). Administration of either antibody alone did not produce this effect. Thymectomy did not alter the degree of intimal proliferation observed in any of the treatment groups. CONCLUSIONS: Our data provide direct evidence that CD8+ T cells are not targeted effectively by CD154 blockade and that the transplant arteriosclerosis seen after CD154 blockade is not due to recent thymic emigrant T cells.